Convective Flow Of Micropolar Fluids Along An Inclined Flat Plate With Variable Electric Conductivity And Uniform Surface Heat Flux (Daffodil International University Journal of Science and Technology, 2011)
Magnetohydrodynamic (MHD) twodimensional steady convective flow and heat transfer of micropolar fluids flow along an inclined flat plate with variable electric conductivity and uniform surface heat flux has been analyzed numerically in the presence of heat generation. With appropriate transformations the boundary layer partial differential equations are transformed into nonlinear ordinary differential equations. The local similarity solutions of the transformed dimensionless equations for the velocity flow, microrotation and heat transfer characteristics are assessed using Nachtsheim- Swigert shooting iteration technique along with the sixth order Runge-Kutta-Butcher initial value solver. Numerical results are presented graphically in the form of velocity, microrotation, and temperature profiles within the boundary layer for different parameters entering into the analysis. The effects of the pertinent parameters on the local skin-friction coefficient (viscous drag), plate couple stress and the rate of heat transfer (Nusselt number) are also discussed and displayed graphically. Keywords: Convective flow; Micropolar fluid; Heat transfer; Electric conductivity; Inclined plate; Locally self-similar solution DOI: http://dx.doi.org/10.3329/diujst.v6i1.9336 DIUJST 2011; 6(1): 69-79